Strategi Social Media Marketing terhadap Brand Image, Brand Trust, dan Brand Awareness dalam Meningkatkan Purchase Intention Travel Umrah - Kurniaty; Usep Suhud; Dewi Agustin Pratama Sari (PT. Hasba Edukasi Mandiri, 2025)
The purpose of this research is to examine the positive and significant influence of social media marketing on brand image, brand awareness, and brand trust in increasing purchase intention. Data were collected through an online questionnaire distributed via social media platforms such as WhatsApp. The object of this research is active social media users who have seen information about Umrah travel services, reside in the DKI Jakarta area, and are at least 17 years old. This study employs a quantitative method with a Structural Equation Modeling (SEM) approach to analyze data from 250 respondents. The findings indicate that social media marketing has a positive and significant effect on brand image, brand awareness, and brand trust in increasing purchase intention for Umrah travel. It is expected that the results of this study can serve as a reference for future research, particularly those related to consumer behavior in Umrah travel services.